CREATIVE LEADERSHIP OF SCHOOL ADMINISTRATORS THAT AFFECT THE EFFECTIVENESS OF SCHOOLS UNDER NAKHON SI THAMMARAT PRIMARY EDUCATIONAL SERVICE AREA OFFICE 3 - Rakkohrung, Natthakit; Thammathikul, Akara; Chatakan, Werayut; Phromnil, Pramote (Journal of Educational Review Faculty of Education in MCU, 2025)
The research article aimed to 1) study the creative leadership of school administrators. 2) study the effectiveness of schools under the Nakhon Si Thammarat Primary Education Service Area Office 3. 3) investigate the impact of creative leadership That Affect the effectiveness Of School, and. 4) explore strategies for developing the Creative Leadership of School Administrators That Affect the Effectiveness of School Under Nakhon Si Thammarat Primary educational Service Area Office 3. The research is Mixed Method 1) Quantitative Research. The sample group used in the research was totaling 310 people. The statistics used for data analysis were frequency, percentage, mean, standard deviation, Person correlation coefficient, and multiple regression. 2) Qualitative Method through interviews with 5 people, analyzing data using content analysis. The research findings revealed that 1) The overall level of creative leadership of administrators is the highest, with all four aspects being rated the highest: vision, creativity, flexibility, and imagination, in that order. 2) The overall effectiveness of the educational institution is at the highest level, with all four aspects being rated the highest: academic achievement, student characteristics, adaptability and school development, and teacher job satisfaction, in that order. 3) The Creative Leadership of School Administrators That Affect The Effectiveness Of School Under Nakhon Si Thammarat Primary educational Service Area Office 3 showed that the key factors were creativity and flexibility and 4) The strategies for developing creative leadership of school Administrators that affect the effectiveness of school under Nakhon Si Thammarat Primary educational Service Area Office 3 (1) vision, school administrators should have foresight, the ability to envision the future, and recognize opportunities for improvement and change to ensure the school progresses and achieves its goals, Set policies that align with educational reform and the changes in today’s society. (2) Creativity: School administrators should be creative, seek new possibilities, invent, and find ways to solve various problems by adapting and developing the institution, while encouraging staff to express their ideas. (3) imagination, School administrators should have a forward-thinking vision and the ability to create mental images, which may lead to new innovations. (4) Flexibility: School administrators should be adaptable to individuals and environments, capable of resolving conflicts, and creating a positive work atmosphere.